Investigations and preparation of fibrinogencoated tanned sheep red cells - Das, P. C. (1970)
The preparation and investigations of tanned sheep red cells coated with human fibrinogen are presented in detail and noted variables are discussed. Both tanning and coating are quick processes. Higher concentrations of tannic acid improved the sensitivity of the cells but required an increased concentration of stabilizing serum to prevent autoagglutination. Fibrinogen concentration above 2 μg/ml had no significant effect, although a concentration above 100 μg/ml sometimes produced cells with incomplete patterns. The pH of the reaction media may be varied widely, although tanning and coating at a more alkaline pH yielded cells showing an indistinct pattern. Cells prepared by this method can be stored for at least six months.